The shaping of rationality in science and religion - Huyssteen, Wentzel J. (Hervormde teologiese studies, 1996)
In this paper the focus is on the extreme epistemological complexity of the relationship between religion and science as two dominant forces in our culture today. This complexity is aggravated by a seemingly conflictual postrnodern, pluralist challenge to a culture that already reveals itself as decidedly empirically-minded. For theology and science a meaningful dialogue becomes possible only if both modes of reflection are willing to move away from overblown foundationalist epistemologies and, for theology at least, from the intellectual coma of fideism. The paper finally argues for a postfoundationalist epistemology where theo-logy and science, although very different modes of reflection, do share the richness of the resources of human rationality. In so doing it attempts to answer three crucial questions: i) are there good reasons for still seeing the natural sciences as our clearest available example of rationality at work? ii) If so, does the rationality of theological reflec-tion in any way overlap with scientific rationality? iii) Even if there are impressive overlaps between these two modes of rationality, how would the rationality of science and the rationality of religious reflection differ?